A study of apnea turn, a new underwater turning method for butterfly and breast stroke races - Taichi, K.; Tsuyoshi, T.; Hideki, T.; Shozo, T. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The present study designed the Apnea turn that carried on the whole body under water to pivot operation and push the wall. This turning method has possibility because it decreased of the wave drag to pivot at under water previously. In addition, the research paper concerning the development of a new turning method like current the Apnea turn is not found. The purpose of this study was to clarify a characteristic of the Apnea turn and to consider about possibility a new turning method for competitive swimmers. METHODS: The subjects were elite competitive swimmers, whose specialties were butterfly and breast stroke. This study calculated that each phase time (turn-in, pivot, glide, turn-out) in the turn phase, push off velocity from the wall, the distance from the wall and the center of gravity, the distance from the water surface to the center of gravity when the wall contact by foot. After the experiment, we implemented subjectively evaluated about the Apnea turn. RESULTS: Average of 5m-RTT was 5.62±0.33s at open turn, 5.55±0.27s at the Apnea turn. The push off velocity from the wall was 2.92±0.06m/s at open turn, 3.02±0.11m/s (p<0.01). Then, nine in ten subjects whose distance of the wall and the center of gravity in the Apnea turn neared than open turn (p<0.01). All subjects whose the water surface and the center of gravity in the Apnea turn was depth than the Open turn (p<0.01). DISCUSSION: The results suggest that the Apnea turn will be able to contribute to improve the swimming performance and then it may become prospective a new turning method. In addition, the Apnea turn has issue to more improve the swimming performance.